Dietary Zinc Is Associated with Cardiac Function in the Older Adult Population - Iwona Szadkowska; Tomasz Kostka; Rafał Nikodem Wlazeł; Łukasz Kroc; Anna Jegier; Agnieszka Guligowska (MDPI AG, 2023)
The elderly is a group at particularly high cardiovascular risk. The coexistence of chronic diseases and use of multiple medications creates the need to look for non-pharmacological agents to improve cardiovascular health in that population. In view of reports on the potential role of zinc in enhancing pathways of myocardial tissue repair, the aim of this study was to evaluate the association between dietary zinc intake and cardiac structure and function in individuals of advanced age. The study group included 251 community-dwelling patients, with a median age of 80 years. Dieta 6.0 software was used for calculation of zinc consumption. Percentage of Recommended Dietary Allowance (RDA) for zinc correlated with left ventricular ejection fraction (LVEF) (r = 0.196, p < 0.05), left ventricular mass index (r = −0.137, p < 0.05) and tricuspid annular plane systolic excursion (TAPSE) (r = 0.153, p < 0.05), while zinc density did so with E/E' ratio (r = −0.127, p < 0.05). In a multiple stepwise regression analysis, the best determinants of LVEF were %RDA for zinc (p = 0.014; β = 0.143), presence of coronary artery disease (p < 0.001; β = −0.39) and age (p = 0.036; β = −0.12). Furthermore, %RDA for zinc (p = 0.009; β = 0.16), female sex (p = 0.005; β = −0.171), beta-blocker use (p = 0.024; β = −0.136), body mass index (p = 0.008; β = 0.16) and heart rate (p = 0.0006; β = −0.209) had an independent effect on TAPSE. In conclusion, in individuals of very advanced age, lower zinc intake is associated with poorer cardiac function. Therefore, increasing the recommended zinc intake in this group deserves consideration.